A study to evaluate risk factors and factors associated with non-adherence to the prescribed treatment among essential hypertensive patients attending tertiary care hospital - Bommishetty, Venkat Sunil; Kumbhar, Suresh Keshav (International Journal Of Community Medicine And Public Health, 2020)
Background: Prevalence of hypertension is on rising trend with rise in life style and behavioral changes. It is also a major risk factor for most of the dreadful conditions like coronary artery disease, stroke, etc. Medication adherence would help in reducing the chance of occurrence of such complications. Thus objectives of study are 1) to evaluate the risk factors of hypertension among the diagnosed essential hypertensive patients; and 2) to assess the magnitude and the factors associated with non-adherence to the prescribed treatment. Methods: A hospital based cross-sectional study among 71 participants was conducted, using a pre-structured questionnaire and physical examination to assess risk factors of hypertension and CULIG’s 16 questionnaire medication adherence scale to assess the non-adherence. Data analysed with proportions and Chi square test. Results: Out of 71 participants, 60 (84.5%) were found to be non-adherent to their anti-hypertensive medication and factors like being male (p=0.0055), alcohol consumption (p=0.0485) and paid medication (p=0.0091) were found to be significantly affecting the medication non-adherence. Positive family history, sedentary life style, preference of extra salt and smoking/tobacco products usage were the most common risk factors of essential hypertension observed along with others. Conclusions: The participants who experienced the complications/ill effects of hypertension were more adherent as compared to others. Factors which are responsible for non -adherence need to be addressed and appropriate interventions required to improve adherence by educating the people about its importance in prevention of complications.